DIGITAL AESTHETIC WAR MACHINES IN SOCIETIES OF CONTROL: PERRIN AND CLUZAUD’S OCEANS (2009) - Konik, Adrian; Konik, Inge (Phronimon, 2017)
This article begins by reflecting on what Gilles Deleuze and Félix Guattari define as aesthetic nomadic war machines, how these war machines relate to the Bergsonian concept of duration, and how they operate to counter State apparatus thought. Examples provided, drawn from Deleuze and Guattari’s work, include the minor literature of Franz Kafka, the intensity art of Francis Bacon, the becoming-animal music of Olivier Messiaen, and what Deleuze identified as modern political cinema – exemplified in the films of Jean Rouch among others. Also thematised is Deleuze’s theorisation of film, particularly its transgressive potential, in Cinema 1: The Movement-Image and Cinema 2: The Time-Image. Focus then shifts to discussion of the further development of scholarship on these ideas, particularly taking into account the rise of digital technologies alongside what Deleuze termed societies of control. Central to such scholarship is contention surrounding whether or not digital media are capable of communicating duration and countering State apparatus thought in a manner akin to their analogue predecessors, in a way that makes the creation of digital war machines possible. After touching on this debate and taking a standpoint in relation to it, the article then moves on to consider Jacques Perrin and Jacques Cluzaud’s film Oceans (2009) as a digital aesthetic war machine.